Women's Vulnerabilities, Women's Voices: Narratives on Patriarchies and Domestic Violence in Assam. Issue 2 (December 2017) - Mahjebeen, Joanna
The article is an attempt to understand the phenomenon of domestic violence through an exploration of the lived experiences and vulnerabilities of women on whom violence had been inflicted in their 'safe havens'. Focusing primarily on domestic violence, the narratives also bring to light the gendered aspects of women's relationship with their family members and expose multiple patriarchies systematically maintained in the family in the context of Assam, a region where women were always thought to enjoy a better status. At a deeper level, the article, while examining a woman's positionality in her own family, also challenges this notion of 'a better status' in the region.